1992
DOI: 10.2165/00003088-199222010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Evaluation of Sustained Release Formulations of Antiepileptic Drugs

Abstract: Epilepsy is a chronic disease that requires long term therapy, and most of the established antiepileptic drugs (the exception is phenobarbital) must be administered several times daily. This results in compliance problems and fluctuations in plasma concentrations which may lead to subtherapeutic and potentially toxic levels. Development of sustained release formulations of the existing antiepileptic agents may improve antiepileptic therapy. At present, only the following 4 major drugs are used for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…This might be improved simply with new drug formulations that enable once‐daily dosing regimens, as has been shown for antiretroviral medications in human immunodeficiency virus (HIV) . In addition to improved adherence, controlled‐release formulations of antiepileptic drugs (AEDs) may prevent or minimize potential intermittent declines in serum concentrations that may be associated with seizure breakthroughs …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This might be improved simply with new drug formulations that enable once‐daily dosing regimens, as has been shown for antiretroviral medications in human immunodeficiency virus (HIV) . In addition to improved adherence, controlled‐release formulations of antiepileptic drugs (AEDs) may prevent or minimize potential intermittent declines in serum concentrations that may be associated with seizure breakthroughs …”
mentioning
confidence: 99%
“…8 In addition to improved adherence, controlledrelease formulations of antiepileptic drugs (AEDs) may prevent or minimize potential intermittent declines in serum concentrations that may be associated with seizure breakthroughs. 9 Pregabalin (PGB) is currently approved as an immediaterelease (IR) capsule in >100 countries, with country-specific indications for adjunctive therapy of partial-onset seizures with or without secondary generalization in adults. The approved dose range in epilepsy is 150-600 mg/day, administered twice daily (BID) or three-times daily (TID).…”
mentioning
confidence: 99%
“…Keywords: antiepileptic drugs, extended-release, modified-release, suffix designations BAC KGRO UND Immediate-release (IR) oral formulations of antiepileptic drugs (AEDs) with short elimination half-lives require frequent administration to maintain the desired therapeutic concentration over the dosing interval and commonly result in large fluctuations in plasma AED concentrations (1)(2)(3).…”
Section: Resultsmentioning
confidence: 99%
“…It is more certain that they minimize concentration-related adverse effects. 3,4 From a patient compliance perspective, it is unknown whether once-daily administration of AEDs is "better" than twice-daily administration. Levy et al demonstrated that switching dosing schedules from multiple doses per day to once daily by the use of ER drug formulations did not generally improve therapeutic coverage.…”
Section: Defining An Optimal Dosing Regimen For Medication Compliancementioning
confidence: 99%
“…2 Some postulate that the ER drug formulations could minimize the undesirable events and increase patient compliance by maintaining flat plasma drug concentrations. 3,4 However, available data suggest that less frequent dosing intervals do not necessarily translate to increased compliance, indicating that side effects and inconvenience alone cannot explain non-adherence.…”
mentioning
confidence: 99%